The Influence of Work Environment and Organizational Commitment on Employee Performance at Alila Villas Uluwatu - Istani, Ni Nyoman Pusti; Sulistyawati, Ni Luh Ketut Sri; Jata, I Wayan (Program Studi Manajemen Divisi Kamar, 2025)
Qualified human resources are the main asset in achieving organizational goals, especially in the highly competitive hospitality industry. Employee performance is a key indicator of organizational success and is influenced by various factors, including work environment and organizational commitment. A supportive work environment can enhance comfort and productivity, while strong organizational commitment encourages employee loyalty and dedication to the company. This study aims to determine the effect of work environment and organizational commitment on employee performance at Alila Villas Uluwatu. This research uses a quantitative approach with a population of 234 employees and a sample of 70 selected by purposive sampling. Data were collected through questionnaires that have been tested for validity and reliability, then analyzed using multiple linear regression, t-test, and F-test with the assistance of SPSS. The results show that work environment and organizational commitment partially have a positive and significant effect on employee performance, and simultaneously, both variables have a significant effect on employee performance with a coefficient of determination of 67%. This study concludes that improving the quality of the work environment and strengthening organizational commitment are effective strategies to encourage employee performance at Alila Villas Uluwatu.